Current Trends i Pharmacology Research - Preclinical Trials: Life Sciences-Pharmacology - Sri.J.V.Krishna Rao, Chief Patron (International Journal of Life Science and Pharma Research, 2020)
This special issue focuses on those aspects with much implication for the healthcare. The articles published in this special issue will certainly bring a positive effect for thedeveloping health care and to make use of available resources and to remove certain obsoletefactors and process which may delay or harm the existing health care system. It enhances maximum utilization of scientific knowledge to potentiate therapy and diagnosis in the healthcare system. Authors presented short review articles as well as research articles in which they focused recent developments in their subject, emphasising the aspects that, in their opinion, are most important. In addition, they provide short annotations to the papers that they consider to be most interesting from all those published in their topic over the previous year. The conference intends to focus on pre-clinical trials. The conference will be offering a unique gathering in respect to scenario of global challenges. It aims to bring together students, teachers, and researchers working in sciences. The conference is expected to be a platform for the gathering of the ideas for the development of clinical research.